Shifting Financial Privileges from Dynasty to Parliament In the Emergence of Modern Turkiye - Barış Bahçeci (Annales de la Faculté de Droit d’Istanbul)
This study deals with the emergence of modern Turkey in the axis of the change in financial privileges. In this respect, the acts of the parliaments are analysed with a descriptive approach. While the parliament conducted the liquidation process of the Ottoman dynasty, it also created some new privileges for its members. This study examines this simultaneous process. The liquidation process started in 1908 with the establishment of a constitutional monarchy initiated by the Committee of Union and Progress (İttihat ve Terakki Cemiyeti). Only after 1920, a national assembly convened under a new leadership in Ankara continued the process and seized the assets of the dynasty, ended tax privileges, and cut their allowances in 1924. However, during the same period, parliament extended the financial status of its members with laws enacted even unconstitutionally. Despite that allowances of MPs were increased, and rules creating pension rights turned into a legislative behaviour that set an example for the following decades too. Moreover, parliament also established financial privileges by tolerating the economic activities of its members. Thus, financial privileges based on blood ties were replaced by another type of privileged status in parallel with the transfer of sovereignty.